Adsorption of Cu(II) ions from aqueous solutions using ion exchange resins with different functional groups. (2nd November 2022) - Elfeghe, Salem; Anwar, Shams; James, Lesley; Zhang, Yahui
Abstract: The extraction of heavy metals from industrial effluents using efficient adsorbents is crucial for wastewater treatment and beneficial for metal recycling. In this study, the removal of Cu(II) from an acidic solution by commercial resins Dowex G‐26 and Puromet™ MTS9570 was investigated. The influences of contact time, solution concentration, pH, temperature, and a resin dosage on the adsorption process were studied with batch technique. The optimum adsorption conditions were obtained at a concentration of 1100 mg/L Cu, contact time of 30 min, pH 3.5, and resin dosage of 0.025 g/ml for the removal of 99.9% and 90% of copper ions by G‐26 and MTS9570, respectively. The experimental data of copper adsorption were analyzed using the Langmuir, Freundlich, and Temkin isotherm models. The highest metal uptakes of 41.67 and 37.70 mg/g were observed for Dowex G‐26 and MTS9570, respectively. It was found that both resins had higher adsorption capacities than the substances reported in the literature. The adsorption kinetic studies showed that the copper adsorption process could be better described by the pseudo‐second order model. Adsorption occurs spontaneously under endothermic conditions, which indicates the endothermic nature of the process.